STEM Approach in Online Lectures: How Does it Contribute to Cognitive Aspects? - Aminah Aminah Zb; Devie Devie Novalian; Edi Edi Rozal; Fauzan Fauzan Sulman; Mhmd Mhmd Habibi (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research uses a STEM approach in online lectures on learning outcomes in biology learning innovation courses. This type of research uses a quantitative approach with a quasi-experimental method with a posttest only design with a nonequivalent group. The population of this study was the fourth-semester students of Tadris Biology UIN Sulthan Thaha Saifuddin Jambi in class VI B and VI C, which opened 18 people. Samples were taken by using a purposive sampling technique. The instrument in this study was in the form of 5 essay test questions. Data analysis used t-test and correlation test. From the results of data analysis with the t test, it can be concluded that online lectures using the STEM approach are much better than online lectures without using the STEM approach. Research analysis continued with correlation test, and it wasfound that lectures with a STEM approach had a significant effect on student cognitive domain learningo utcomes.Keywords: Online Lectures, STEM Approach, Cognitive Learning Outcomes